APPLICATION OF GREENCOMPOST FOR IMPROVEMENT IN SOIL CHEMICAL PROPERTIES AND FERTILITY STATUS - G. Sarwar; H. Schmeisky; M. A. Tahir; Y. Iftikhar; N. U. Sabah (Journal of Animal and Plant Sciences, 2010)
Green compost is prepared from green wastes such as garden and farm wastes. This compost was analyzed (pH= 7.3 and C: N ratio = 10.19:1) before its application to soil. A pot experiment was conducted to assess the efficiency of green compost to improve chemical properties of soil. Three types of soils were used for this purpose. Green compost was applied to each soil type @ 5 and 10 % of soil volume. Lolium perenne grass was grown in all the pots those were replicated four times arranged in CRD factorial.. After harvesting the grass, soil samples were also taken from all the pots and analyzed for pH, EC, organic matter, N, C, C/N ratio and mineral nutrients (Ca, Mg, K, P & Cl). Results revealed that use of green compost at both the levels (5 and 10 %) increased soil pH and EC. Organic matter, N and C %age were enhanced with a net decrease in C/N ratio. Contents of mineral nutrients of the soil also increased by the addition of green compost. Resultantly, an improvement in soils chemical properties was noticed.
Keywords: Green compost; soil pH; EC; organic matter; C/N ratio and mineral nutrients (Ca; Mg; K; P & Cl)